2016
DOI: 10.2147/dddt.s114879
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide inhibits macrophage inflammatory mediators and controls hypertension in spontaneously hypertensive rats via the peroxisome proliferator-activated receptor gamma pathway

Abstract: Fenretinide is a novel anticancer agent reported to exhibit anti-invasive and antimetastatic activities. It has also been shown to improve obesity and diabetes, although the effects of fenretinide on hypertension are still unknown, and the detailed mechanisms remain unclear. In this study, we have shown that treatment with lipopolysaccharide (LPS) decreased the expression of peroxisome proliferator-activated receptor γ (PPARγ) in RAW264.7 macrophages, and pretreatment with fenretinide reversed the effect of LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 92 publications
(74 reference statements)
4
16
0
Order By: Relevance
“…On the other hand, we demonstrated for the first time that 9-oxo-ODA was not only a PPARα activator but also showed anti-inflammatory properties. In addition, previous studies have reported that PPARγ the subtype of PPARα, is likely to be concerned with anti-inflammatory effect in LPS-stimulated macrophages[ 41 , 42 ]. Therefore, we investigated whether the anti-inflammatory activities of 9-oxo-ODA participated in PPARα and PPARγ by using antagonist with reference to the previous studies[ 19 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we demonstrated for the first time that 9-oxo-ODA was not only a PPARα activator but also showed anti-inflammatory properties. In addition, previous studies have reported that PPARγ the subtype of PPARα, is likely to be concerned with anti-inflammatory effect in LPS-stimulated macrophages[ 41 , 42 ]. Therefore, we investigated whether the anti-inflammatory activities of 9-oxo-ODA participated in PPARα and PPARγ by using antagonist with reference to the previous studies[ 19 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have reported that PPARγ the subtype of PPARα, is likely to be concerned with anti-inflammatory effect in LPS-stimulated macrophages[ 41 , 42 ]. Therefore, we investigated whether the anti-inflammatory activities of 9-oxo-ODA participated in PPARα and PPARγ by using antagonist with reference to the previous studies[ 19 , 42 ]. The anti-inflammatory activities of 9-oxo-ODA on NO production was unchanged by PPARα antagonist GW6471 and PPARγ antagonist GW9662 ( S4A and S4B Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, fenretinide has been shown to inhibit growth in lung cancer cell lines [38] and it has been proposed as a potential adjuvant for late onset Alzheimer's disease [39]. Moreover, the fenretinide community is tightly linked with the monocytes one, in agreement with its mechanisms of action involving the regulation of the secretion of pro-inflammatory cytokines in human monocytes [40].…”
Section: New Biological Insights On the Inverse Comorbidity Between Amentioning
confidence: 88%
“…The communities associated to mitochondria span different processes related to their activity: oxidation-reduction process (communities 16,23,40), hypoxia (community 10) and phosphate metabolic process (community 38). Enrichment in hypoxia could correspond to a confounding factor linked to the state of the profiled tissues (post-mortem for AD and fresh tissue biopsy for LC).…”
Section: New Biological Insights On the Inverse Comorbidity Between Amentioning
confidence: 99%
“… 7 In addition, fenretinide decreased lipopolysaccharide (LPS)-induced proinflammatory cytokine production, including tumor necrosis factor-α, interleukin 6 (IL-6), and monocyte chemoattractant protein 1, nitric oxide synthase expression, and nitrogen oxide production through activating peroxisome proliferator-activated receptor γ in macrophages. 8 Moreover, inflammation and airway hyperresponsiveness induced by ovalbumin were protected by fenretinide, which completely blocked inflammatory cell recruitment into the airways and distinctly reduced goblet cell proliferation. 9 …”
mentioning
confidence: 97%